Climate change adaptation, gender, and mainstreaming: the role of gender in Fiji's relocation initiative - Bertana, Amanda; Blanton, Natalie (Climate and Development, 2022)
Climate change has elucidated already existing gender inequalities associated with unequal access to resources, decision-making processes, and higher exposure to environmental shocks and stressors. Growing acknowledgment of the gender-differentiated implications of climate change in recent years has placed gender equality as a focal point in international discourses on climate change adaptation. The policy perspective of gender equality is universalized, but how it transcribes in local climate change adaptation projects remains elusive. Using the relocation of Vunidogoloa, Fiji, this article explores the tension and compatibility between the way gender equality is discussed and how it is implemented in climate change adaptation projects.
Keywords: Climate change; Fiji; adaptation; dept.soc; gender equality; gender mainstreaming; peer-reviewed; relocation; sea level rise

Beyond maladaptation: structural barriers to successful adaptation - Bertana, Amanda; Clark, Brett; Benney, Tabitha M.; Quackenbush, Cameron (Environmental Sociology, 2022)
Around the world adaptation projects are being implemented, with the hope of essentially climate proofing communities. While there is an abundance of failed adaptation schemes in developing and developed countries alike, there has been little scholarship on this problem. Through interviews with twenty-two climate change adaptation practitioners, we identify four structural challenges that contribute to maladaptation: the focus on technological fixes versus holistic approaches; the difficultly of distinguishing between adaptation and development; the problem of quantifying non-quantifiable variables; and the existence of competing problems given that failure to mainstream climate change adaptation. Addressing these maladaptation dynamics is necessary to enhance successful adaptation processes.
Keywords: SCSU Faculty Scholar Award; award_winner; climate change; climate change adaptation; dept.soc; development; maladaptation; peer-reviewed; policy

The US Blue New Deal: What does it mean for just transitions, sustainability, and resilience of the blue economy? - Axon, S.; Bertana, A.; Graziano, M.; Cross, E.; Smith, A.; Axon, K.; Wakefield, A. (Geographical Journal, 2022)
The ocean and coasts are largely absent from the “Green New Deal” proposal. In response to the limited attention paid to the sustainability and equitable governance approaches of the blue economy, a US “Blue New Deal” has been proposed aiming to protect the health of the ocean and support coastal communities' adaptation to climate change. The Blue New Deal emerged as a central policy proposal from 2020 Democratic presidential candidate Elizabeth Warren to enhance the role of the blue economy while simultaneously addressing the climate crisis. Through a just transitions analysis, this article evaluates the proposal for a US Blue New Deal — as designed by Senator Elizabeth Warren — that would be applied towards enhancing socioeconomic resiliency, environmental justice, and addressing social inequities. As part of a critical policy analysis evaluating the areas of focus Warren's Blue New Deal presents, environmental justice and sustainability are central to the success of managing, and enhancing the role of, the blue economy. The challenges facing the Blue New Deal reflect a “one size fits all” federal approach that has implications for addressing multifaceted obstacles in key sectors of the blue economy, its governance, and tackling interconnected crises that exacerbate socioeconomic inequities and vulnerabilities of marginalised coastal communities. This article proposes a blue justice framework for the Blue New Deal that seeks to address the tensions and contradictions that exist in its current form and indicates how a comprehensive policy framework can enhance the sustainability and equitable involvement of the blue economy. The information, practices and views in this article are those of the author(s) and do not necessarily reflect the opinion of the Royal Geographical Society (with IBG). © 2022 Royal Geographical Society (with the Institute of British Geographers).
Keywords: dept.egm; dept.mgt; dept.soc; peer-reviewed